Rancang Bangun Aplikasi Inventory Berbasis Website Pada Kreasitex Jakarta - Robert Robert; Prya Artha Widjaja (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
This study aims to design and build an inventory application that can support buying and selling activities at the Kreasitex Jakarta company. Ms. Margaretha Christie served as a resource person in this study to provide information regarding research needs as a deputy director of the company. The waterfall design method is used in this study and uses the javascript and golang programming languages. The functionality testing method is used to test the application. The result of this research is the development of an inventory application that simplifies the buying and selling process and helps record the stock of goods. This inventory system is also useful in managing goods purchased by customers. This application supports the development of the company wit h its good functionality. Overall, this study concludes that this inventory application supports the activities of buying and selling, storing, recording, and managing stock of goods. With the inventory application, the sales process becomes more practical and efficient.